Genomic Approach to Asthma (Translational Bioinformatics,, 2018)
This volume in the series, Translational Bioinformatics, provides an up-to-date overview of genomic approaches to asthma. By applying unbiased "-omics" combined with disease-focused and hypothesis-driven approaches, it enhances readers' understanding of the asthma endotype. Furthermore, it elucidates how progress in -omics research, such as "genomic," "transcriptomic," "protomic," and "metabolomic," is applied in asthma, and reports on the related series of important breakthroughs in asthma development, classification, prevention and drug sensitivity. Also covering systems biology knowledge and methodologies, computational models and biostatistical methods to analyze big data, this book provides a valuable resource for scientists and researchers in the field of asthma and respiratory diseases.